Haematoma, Abscess or Meningitis After Neuraxial Anesthesia in the USA and the Netherlands: A Closed Claims Analysis. Issue 2 (June 2021) - Bos, E.M.sE.; Posner, K.L.; Domino, K.B.; de Quelerij, M.; Kalkman Cor, J.; Hollmann, M.W.; Lirk, P.
Abstract : ( Eur J Anaesthesiol . 2020;37:743–751) Current anesthesia practice often involves neuraxial techniques such as spinal anesthesia and epidural analgesia. The leading anesthetic technique for cesarean delivery remains spinal anesthesia, while chronic pain treatments include spinal cord stimulators, epidural injections, and intrathecal drug delivery systems. The rarest but most feared complication of these techniques is injury to the spinal cord via neuraxial abscess or hematoma, but possible other complications include medication errors, meningitis, and even direct nerve injury. The primary aim of this study was to identify possible preventable causes of hematoma and abscess, meningitis, and other serious adverse outcomes following neuraxial procedures by analyzing claims databases in two countries: The Anesthesia Closed Claims Project database in the USA, and the Netherlands' two largest medical insurance companies' databases.